Playing in the New Media Game or Riding the Virtual Bench: Confirming and Disconfirming Membership in the Community of Sport. (February 2015) - Kassing, Jeffrey W.; Sanderson, Jimmy
This essay explores a set of new media user trends that are (re)shaping fan–athlete interaction through (para)social connections. Acting as bonding agents, the trends considered either contribute to or detract from membership in the community of sport. Accordingly, social leveling practices, invitational uses, and bridging functions serve to connect people within the community of sport, whereas policing, maladaptive parasocial interaction, and hypermasculinity function to disconnect people from the community of sport. The essay looks at these trends in detail and provides examples of each in practice. It concludes with a discussion of the digital literacy implications that fan–athlete interaction via new media introduces.